Mass Spectrometry Guided Discovery and Design of Novel Asperphenamate Analogs From Penicillium astrolabium Reveals an Extraordinary NRPS Flexibility - Subko, Karolina; Wang, Xinhui; Nielsen, Frederik H.; Isbrandt, Thomas; Gotfredsen, Charlotte H.; Ramos, Maria C.; Mackenzie, Thomas; Vicente, Francisca; Genilloud, Olga; Frisvad, Jens C.; Larsen, Thomas O. (Frontiers in Microbiology, 2021)
Asperphenamate is a small peptide natural product that has gained much interest due to its antitumor activity. In the recent years numerous bioactive synthetic asperphenamate analogues have been reported, whereas only a handful of natural analogues either of microbial or plant origin has been discovered. Herein we describe a UHPLC-HRMS/MS and amino acid supplement approach for discovery and design novel asperphenamate analogues. Chemical analysis of Penicillium astrolabium, a prolific producer of asperphenamate, revealed three previously described and two novel asperphenamate analogues produced in significant amounts, suggesting a potential for biosynthesis of further asperphenamate analogues by varying the amino acid availability. Subsequent growth on proteogenic and non-proteogenic amino acid enriched media, revealed a series of novel asperphenamate analogues, including single or double amino acid exchange, as well as benzoic acid exchange for nicotinic acid, with the latter observed from a natural source for the first time. In total, 22 new asperphenamate analogues were characterized by HRMS/MS, with one additionally confirmed by isolation and NMR structure elucidation. This study indicates an extraordinary nonribosomal peptide synthetase (NRPS) flexibility based on substrate availability, and therefore the potential for manipulating and designing novel peptide natural products in filamentous fungi.